Optimization of Shrimp Cracker Drying Parameters Using RSM and RCA: Optimasi Parameter Pengeringan Kerupuk Udang Menggunakan RSM dan RCA - Andreyanto, Muhammad Faisal; Sulistiyowati, Wiwik (Indonesian Journal of Innovation Studies, 2025)
General Background Shrimp cracker production requires strict quality control, particularly in moisture content, which determines texture, shelf life, and defect occurrence. Specific Background In industrial practice, defects such as mold growth remain a critical issue due to suboptimal drying and process control conditions. Knowledge Gap Previous studies have not fully integrated process optimization and root cause identification to address both quality parameters and defect sources simultaneously. Aims This study aims to optimize drying parameters and identify root causes of defects using Response Surface Methodology (RSM) and Root Cause Analysis (RCA). Results The optimal conditions were obtained at a temperature of 70°C, drying time of 60 minutes, and thickness of 5 mm, producing a moisture content of 9.00% with a desirability value of 1.00. RCA findings indicate that mold defects are caused by high raw material moisture, inadequate storage conditions, and limited production supervision. Novelty This study integrates RSM-based parameter optimization with RCA-based defect analysis within a single framework. Implications The results provide practical recommendations for improving production control, reducing defects, and maintaining consistent product quality in shrimp cracker manufacturing. Keywords: Shrimp Cracker, Process Optimization, Moisture Content, Response Surface Methodology, Root Cause Analysis Key Findings Highlights Optimal drying parameters identified through statistical modeling approach Major defect source linked to raw material and process control conditions Integrated analytical framework supports systematic quality improvement